Cortical Mechanisms of Tongue Sensorimotor Functions in Humans: A Review of the Magnetoencephalography Approach - Maezawa, Hitoshi (Frontiers in Human Neuroscience, 2017)
The tongue plays important roles in a variety of critical human oral functions, including speech production, swallowing, mastication, and respiration. These sophisticated tongue movements are in part finely regulated by cortical entrainment. Many studies have examined sensorimotor processing in the limbs using magnetoencephalography (MEG), which has high spatiotemporal resolution. Such studies have employed multiple methods of analysis, including somatosensory evoked fields, movement-related cortical fields, event-related desynchronization/synchronization associated with somatosensory stimulation or movement, and cortico-muscular coherence during sustained movement. However, the cortical mechanisms underlying the sensorimotor functions of the tongue remain unclear, as contamination artifacts induced by stimulation and/or muscle activity within the orofacial region complicates MEG analysis in the oral region. Recently, several studies have obtained MEG recordings from the tongue region using improved stimulation methods and movement tasks. In the present review, we provide a detailed overview of tongue sensorimotor processing in humans, based on the findings of recent MEG studies. In addition, we review the clinical applications of MEG for sensory disturbances of the tongue caused by damage to the lingual nerve. Increased knowledge of the physiological and pathophysiological mechanisms underlying tongue sensorimotor processing may improve our understanding of the cortical entrainment of human oral functions.